2018
DOI: 10.18502/sjms.v13i1.1686
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of hepatitis (B) among healthcare workers in relation to their vaccination status in Khartoum, Sudan, 2015: a cross-sectional study

Abstract: Background: Hepatitis B is a serious chronic infection of the liver and caused by hepatitis B virus. It is an endemic disease in Sudan. Healthcare workers are occupationally[MS1]  more prone to acquire the disease. Evaluation of their knowledge, attitude and practice, and their vaccination status, are very important in the control of the disease. The aim of this study is to assess the knowledge, attitude, and practice of healthcare workers towards hepatitis B and their vaccination status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
1
2
2
1
Order By: Relevance
“…The results of the current study revealed a significant association between HCW category, level of education and knowledge on the route of HBV transmission. This is similar to what was obtained in Sierra Leone,11 Sudan19 and Northeast Ethiopia 20. This may be justified by the fact that education trains individuals to acquire, evaluate and use information 21.…”
Section: Discussionsupporting
confidence: 82%
“…The results of the current study revealed a significant association between HCW category, level of education and knowledge on the route of HBV transmission. This is similar to what was obtained in Sierra Leone,11 Sudan19 and Northeast Ethiopia 20. This may be justified by the fact that education trains individuals to acquire, evaluate and use information 21.…”
Section: Discussionsupporting
confidence: 82%
“…Based on our study majourty of study participants, 279 (65.6%) had good knowelege towards HBV infection. This finding was inconsistance with the study done in Mogadishu Somalia (80.9%) [ 12 ], Northern Nigeria (76.9%) [ 6 ], and khartoum, Sudan (70.0%) [ 13 ], respectively. This is maybe the difference in the educational status of the study population.…”
Section: Discussioncontrasting
confidence: 83%
“…According to this study's findings, the HBV vaccine's widespread sensitization campaigns carried out by the Ugandan Ministry of Health in recent years may be to blame for the high level of knowledge about its availability among healthcare professionals at Gulu Regional Referral Hospital (Morris et al 2021) [25] . Regarding the respondents checking the efficiency of the vaccination after vaccination in our study is very low and mainly by medical staff (15%) in comparison with the study of Almustafa, et al, 2015 [16] This study revealed that 71.3% did not obtain the post-vaccination test to ensure the efficiency of the vaccination. Our study reveals higher results than the study of Ali AL-Janabi, 2009 [20] found that in Karbala, all laboratory workers gave negative results after ELISA assaying blood, and only two male technicians at Al-Hussein general hospital showed positive IgG anti-HBsAg, which may be related to vaccine response.…”
Section: Discussioncontrasting
confidence: 73%